Embrassing Stories - A Blue Film - Silvester Goridus Sukur (KANISIUS, 2009)
A Blue Film is a collection of embrassing short stories. You are going to read short about incidents or events which are so embrassing that will make you smile, giggle, or even roar with laughter.